ANALISIS TINGKAT PENYERAPAN TENAGA KERJA PADA SENTRA KERAJINAN EMAS SEKARBELA KELURAHAN KARANG PULE KECAMATAN SEKARBELA - M. Erhan Dwitya Sanrima (Fakultas Ekonomi Universitas Islam Al-Azhar, 2021)
This study is entitled Analysis of Crafters' Income and Absorption Levels at Sekarbela Gold Craft Center, Karang Pule Village, Sekarbela District. This study aims to determine the level of income that affects the workforce at the Sekarbela gold craft center, Karang Pule Village, Sekarbela District. To find out the amount of labor absorption in the gold craft center in Sekarbela, Karang Pule Village, Sekarbela District. This type of research is associative with a quantitative approach. The data collection technique uses a questionnaire in the form of a questionnaire. Data analysis using simple linear regression, which consists of one independent variable and one dependent variable, namely the income variable (X) and the labor variable (Y). The results of this study that partially obtained very convincing results, namely income has a tcount of 1.459 with sig. t is 0.000 (p <0.05) which is below 5% and the t table value is seen by consulting the product moment label based on the 5% significance level, then the t table number = 0.246. This means that there is a significant influence between income and labor absorption at the Sekarbela gold craft center, Karang Pule Village, Sekarbel District. This shows that the higher the income, the higher the employment of the gold handicraft center in Sekarbela, Karang Pule Village, Sekarbel District. Whereas the average employment is 14 people or 14 HKO. This shows that the amount of labor absorption in the gold handicraft center if it is adjusted to the Sokartawi criteria used falls into the less large category, namely ≤ 25%. This means that gold handicraft activities in Sekarbela are less able to absorb labor.